Serving each other: Sharing economies and affective labour in montréal's kiki scene - Lundy, Jesse D. (Université Carleton, 2019)
Against a tense socio-political backdrop of white supremacy, intensifying pressures of neoliberal fiscal austerity, and queer necropolitics, this thesis addresses performance-based activist forms of place-making for urban-based queer, trans, and gender nonconforming communities of colour. Using participant observation and qualitative interviews with pioneering members of Montréal’s Kiki scene and Ottawa’s emerging Waacking community and interpreting my findings through the theoretical lens of queer of colour theory, critical whiteness studies, queer Latinx performance studies and Chicana feminism, I argue that Kiki subculture, which is maintained by pedagogical processes of ‘each one, teach one’, is instrumental in facilitating i) life-affirming queer kinship bonds, (ii) alternative ways to simultaneously embody and celebrate nonnormative gender expression with Black, Asian, and Latinx identity, iii) non-capitalist economies of sharing, and iv) hopeful strategies of everyday community activism and resilience to appropriative processes during economic insecurity and necropolitical turmoil.
https://doi.org/10.22215/etd/2020-13975
Keywords: LGBTQIA2+; approches et analyses; discours dominant; ethnologie; identités LGBTQIA2+; militance; montréal; mémoires/thèses; ottawa; queer; queer of color; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; étude qualitative; études culturelles

Le Coran et la femme : relire le Coran du point de vue de la femme - Wadud, Amina (Éditions Tarkiz, 2019)
Le Coran et la femme est la traduction du premier ouvrage d'Amina Wadud, Quran and Woman, dans lequel elle livre un travail pionnier, fondateur du féminisme islamique occidentale, qui demeure d'autant plus pertinent à l'heure du mouvement "MeToo" . Du point de vue du genre, il est probablement un des premiers commentaires du Coran réalisé par une femme dans une discipline historiquement dominée par les hommes. Sous l'angle de la méthode, il développe une approche originale en ce qu'il mobilise un appareil herméneutique en rupture avec les commentaires traditionnels qui sont de type analytique. Sur le fond, l'ouvrage ouvre la voie à une série de travaux s'intéressant à la question de la femme dans le Coran, et en particulier, dans les sociétés occidentales. Sans que ce ne soit son objectif principal, il déconstruit également un grand nombre de clichés relatifs aux femmes musulmanes dans les sociétés occidentales et démontre qu'ils ne prennent pas leur source dans le Coran.
Keywords: approches et analyses; cours; discipline; fem3400; féminisme islamique; genre; identités LGBTQIA2+; premier cycle; science des religions; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques